2012
DOI: 10.3109/19396368.2012.656797
|View full text |Cite
|
Sign up to set email alerts
|

Birth and clinical pregnancy from fresh and frozen oocytes fertilized with cryopreserved testicular spermatozoa

Abstract: This is the first report showing a second clinical pregnancy of a couple who already have a baby from a previous frozen embryo transfer cycle when the embryos were generated from fresh oocytes that were fertilized by intracytoplasmic sperm injection (ICSI) using frozen testicular spermatozoa (the couple have unsuccessful fresh and frozen embryo transfer cycles). Fifty-two months after the first IVF/ICSI cycle the couple had their second IVF/ICSI cycle, but the collected oocytes (n=8) were frozen because no spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The results indicated that no additional DNA damage was produced during cryopreservation using Cryopiece. DNA fragmentation could lead to embryo development stop and abortion (20,21). In our previous work, it had been proved that cryopreservation of sperm using micro-straw or ministraw would not impair sperm DNA integrity (7).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that no additional DNA damage was produced during cryopreservation using Cryopiece. DNA fragmentation could lead to embryo development stop and abortion (20,21). In our previous work, it had been proved that cryopreservation of sperm using micro-straw or ministraw would not impair sperm DNA integrity (7).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation protocols, oocyte recovery, and ET techniques were used as previously described [315]. Briefly, all patients were treated with controlled ovarian stimulation by a gonadotropin-releasing hormone antagonist protocol using a starting dose of 225 IU of recombinant follicle-stimulating hormone (rFSH) (Gonal F; Merck Serono, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Indications for IVF-ET were: male factor (40%), tubal factor (34%), endometriosis (15%) and unexplained infertility (11%). The reader is referred to our previous publications for stimulation protocols, oocyte recovery and ET techniques (Kanyo & Konc, 2003;Konc et al, 2005Konc et al, , 2010Zeke et al, 2012).…”
Section: Patient Selection Controlled Ovarian Stimulation Oocyte Rementioning
confidence: 99%
“…Pregnancy was defined as a spontaneous rise in a ␤-hCG concentration at least 10 days post-transfer. Clinical pregnancy implied the presence of an intrauterine gestational sac and fetal heart beat on an ultrasound performed at 7 weeks of gestation (Zeke et al, 2012). In case of spontaneous abortion, the patient lost her biochemical or clinical pregnancy.…”
Section: Endometrial Preparation and Transfer Of Frozen-thawed Embryosmentioning
confidence: 99%
See 1 more Smart Citation